Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China - Ren, Jin-Long; Wang, Kai; Nguyen, Tao Thien; van Hoang, Chung; Zhong, Guang-Hui; Jiang, Ke; Guo, Peng; Li, Jia-Tang (Zootaxa, 2018)
The Asian monotypic genus Pararhabdophis Bourret, 1934 has long been known from a single holotype of the type species Pararhabdophis chapaensis Bourret, 1934 only. The limited available information hampered the identification of the natricine species. On the basis of eight newly collected specimens of P. chapaensis from the type locality in Sa Pa, Lao Cai Province, Vietnam and from Pingbian, Yunnan Province in southwestern China, the taxonomic position of the genus Pararhabdophis was re-evaluated using both morphological and molecular datasets for the first time. Pararhabdophis chapaensis is nested within the genus Hebius Thompson, 1913 with strong support, and morphologically indistinguishable from the latter genus. As a consequence, we herein synonymize the genus Pararhabdophis with Hebius and discuss about the existing paraphyly of some Hebius species. In addition we report Hebius chapaensis for the first time from China and provide redescription and natural history data of this poorly known species. To facilitate future taxonomic work, an identification key to all known natricine genera from China and Vietnam is also provided.